Mahar Berupa Perkataan dalam Perkawinan di Kepulauan Sula Perspektif Hukum Keluarga Islam - yulianti yulianti (Al-Mizan: Jurnal Kajian Hukum dan Ekonomi, 2026)
This article examines the practice of verbal dowry (mahar berupa perkataan) in Muslim marriages in the Sula Islands Regency, North Maluku, Indonesia. Verbal dowry—a spoken promise made by the groom as the marriage gift—represents a rarely documented phenomenon in Islamic legal literature. The study aims to describe the implementation mechanism of verbal dowry and analyze its legal validity from the perspective of Islamic family law, encompassing the views of classical jurists, the Compilation of Islamic Law (KHI), local religious scholars, and the theory of maslahah mursalah. Using a qualitative field research approach on five marriage cases, the study finds that verbal dowry is pronounced during the marriage contract yet is consistently replaced with material dowry at the urging of Religious Affairs Office officials and local scholars. All reviewed Islamic legal perspectives reject the validity of verbal dowry as it fails to satisfy the requirements of qimah (material value) and tamlik (transferability), despite containing psychological benefit for the wife.